Association of Diabetes Mellitus and Pancreatic Cancer: Literature Review - Pastorello, Julia; Lando, Emanuela; Gervaso, Lorenzo; Fazio, Nicola (Brazilian Journal of Case Reports, 2023)
Despite the metabolic activity, especially related to endocrinological disease, diabetes mellitus seems to be intrinsically associated with pancreatic cancer, studies in this line of research are still limited and without a detailed description of the disorders that confirm the association between them. Thus, the present study aims, in essence, through the literature review method, to present the association of pancreatic neoplasia and diabetes mellitus, seeking to evaluate the mechanism of association between the endocrinological presentation studied as a causality factor or possible consequence in the face of the neoplasm condition, as well as evaluating the possibility of screening, according to associative confirmation, of patients with diabetes mellitus in relation to the development of pancreatic cancer, considering that this neoplasm has one of the highest mortality rates ever described in the literature.